Audit Sistem Keamanan Jaringan Pada PT TRIAS SENTOSA TBK - Michael Setiono; Leo Willyanto Santoso; Agustinus Noertjahyana (Jurnal Infra, 2016)
PT Trias Sentosa was founded in 1979. The company is dealing with manufacturing and production of plastics, During the last year to date, PT. Trias Sentosa Tbk has used a security system that is highly controlled and has been tested kelayakanya communication between each warehouse to a central server. However, sometimes the data from BOPPET that go into servers sometimes experience an error or what is often called "bugs" this causes their data and data terduplikat less valid, but each day PT Trias itself made of plastic with a large number. Therefore, the Information Systems Audit and ISO (International Organization for Standardization) to a solution to measure whether the security of application systems that exist within the company in accordance with the standards that have been internationally recognized that IT governance contained in the COBIT (Control Objectives for Information and Related Technology). COBIT is a framework for information technology published by ISACA (Information Systems Audit and Control Association) and is used because it has a high level of complexity and coverage. As well, in this analysis, the domain used is based on COBIT Deliver and Support. Then from that domain, the discussion is limited to the level DS5 (Ensure Security Systems). And to ISO itself is limited by ISO 27002 (Information Security Management System.)